Determination of the tensile and fracture properties of ductile materials by small punch testing. Issue 7 (3rd July 2021) - Peng, Yun-Qiang; Jia, Dong; Wang, Luo-Bin; Wei, Li-Ming
ABSTRACT: The uniaxial tensile and fracture properties are the basic data for the structural integrity assessment of ductile material. In this study, the stress-strain relations of ductile materials are predicted by the SPT-related stress-strain relation (SPT-SR) model directly through SPT experiment, which agree with the relations determined by the finite-element-analysis aided testing (FAT) method. Further, the experimental procedures of SPT are simulated by combining the Gurson-Tvergaard-Needleman (GTN) model and the predicted stress-strain relations. The parameters of GTN model can be determined when the simulated load-displacement curves of SPT specimens coincide with the experimental results. Finally, the ductile crack propagation behaviors of the single edge-notched bending (SEB) specimens are simulated utilizing the calibrated GTN model, and the corresponding J resistance curves are successfully predicted via the normalization method.